Nurses’ Attitudes and Knowledge of Peripherally Inserted Central Catheter Maintenance in Primary Hospitals in China: A Cross-Sectional Survey - Xu B; Zhang J; Hou J; Ma M; Gong Z; Tang S (Dove Medical Press, 2020)
Binbin Xu,1,2 Jinghui Zhang,1,3 Jianmei Hou,2 Mengdan Ma,2 Zhihong Gong,2 Siyuan Tang2 1Teaching and Research Office of Clinical Nursing, Xiangya Hospital of Central South University, Changsha, Hunan, People’s Republic of China; 2Xiangya Nursing School, Central South University, Changsha, Hunan, People’s Republic of China; 3National Clinical Research Center for Geriatric Disorders, Xiangya Hospital, Central South University, Changsha, Hunan, People’s Republic of ChinaCorrespondence: Jinghui ZhangTeaching and Research Office of Clinical Nursing, Xiangya Hospital of Central South University, Changsha 410008, People’s Republic of ChinaTel +86 15874032339Email zhangjh-1206@163.comBackground and Aim: The promotion of peripherally inserted central catheter (PICC) maintenance in primary hospitals can benefit discharged patients with PICCs living in remote areas a lot. Yet, no primary hospitals had introduced PICC maintenance technology in Hunan province, China. The present study aimed to evaluate nurses’ attitudes and knowledge of PICC maintenance in primary hospitals in Hunan province, China.Materials and Methods: From November 2018 to January 2019, a total of 560 nurses from 28 community hospitals and 28 township hospitals in 14 cities across Hunan were recruited in the present study. All nurses were registered nurses engaged in clinical work related to intravenous infusion, and their attitudes and knowledge of PICC maintenance were measured by a self-designed questionnaire that was based on literature review and expert consultation.Results: The response rate was 93.6% (560 of 598). Almost all participants could realize the importance and necessity of PICC maintenance. More than 90% of the participants expressed interest in PICC maintenance and showed strong demands for relevant training. However, the nurses’ correct response rate of most knowledge items was at a low level (7.14– 57.68%), with only three items exhibiting the correct response rate of 90% or higher. The factors influencing the nurses’ PICC maintenance knowledge included their nursing experience, professional title, work setting, and department.Conclusion: Although nurses in primary hospitals had a positive attitude toward PICC maintenance, their knowledge level was unsatisfactory, which might be a barrier to the promotion of PICC maintenance technology in primary hospitals in Hunan province, China. Multiple parties should get involved and take measures to improve the nurses’ PICC maintenance knowledge, including the government, nursing associations, large-scale hospitals, and primary hospitals themselves. Besides, new training models and dynamic assessment methods should be explored to improve training effectiveness in the future.Keywords: attitudes, catheter maintenance, knowledge, nurses, peripherally inserted central catheter, PICC, primary hospitals